Impact of Supply Chain Integration in Enterprise Resource Planning Systems that Affect Company Performance - Zalfa, Dhia (Journal La Multiapp, 2023)
PT Sumber Graha Sejahtera, Way Kanan, Lampung often experiences unfulfilled production targets and customer demands. Many customers give complaints because the number of products sent by the company does not match the desired amount. The purpose of this study was to determine the direct effect of the ERP system on company performance, and the indirect effect of the ERP system on company performance mediated by supplier integration, internal integration, and customer integration. This research uses quantitative methods. The population in this study were all employees at PT Sumber Graha Sejahtera, Way Kanan, Lampung, totaling 340 people. The sample size was calculated using the Yamane and Isaac formula which resulted in 184 employees. Samples were taken using purposive sampling technique. The data analysis technique used is Structural Equation Modeling (SEM)-Partial Least Square (PLS). The results of the study show that ERP has a direct, significant effect on firm performance. In addition, ERP has no significant effect on firm performance through supplier integration, internal integration and customer integration. PT Sumber Graha Sejahtera must improve the management of management resources well, increase performance improvement, and build business innovation, so that corporate decision making can be effective for all related parties. With the implementation of good resource planning, the company will no longer receive complaints from customers.